Transition metal oxide catalyst taking biomass as surface structure control agent and application of transition metal oxide catalyst in low-temperature catalytic decomposition of N2O

By using biomass as a surface structure control agent in cobalt-based oxide catalysts and preparing through the sol-gel method, the problems of catalyst activity and impurity resistance are solved, and efficient N2O decomposition and impurity resistance are achieved, especially It exhibits excellent catalytic activity and stability at low temperatures.

CN119303578APending Publication Date: 2025-01-14LIAONING UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411412771.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing cobalt-based oxide catalysts have low activity when catalyzed decomposition of N2O, complex processes, high cost, and difficult to have high catalytic activity and anti-impact gas properties at the same time.

Method used

Using biomass as the surface structure control agent, the transition metal oxide catalyst is prepared by the sol-gel method, and the chemical reaction between agar and transition metal oxide is used to reduce the grain size, increase the specific surface area and active sites, and weaken the Co-O bonds form oxygen vacancies and lattice defects.

Benefits of technology

The catalytic activity and impurity gas resistance of the catalyst are improved, and N2O can be efficiently decomposed at low temperatures, and the conversion rate remains high when the impurity gas is present, for example, the N2O conversion rate reaches 51% at 400°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303578A_ABST
    Figure CN119303578A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalytic decomposition of N2O, in particular to a transition metal oxide catalyst with biomass as a surface structure control agent and application of the transition metal oxide catalyst in low-temperature catalytic decomposition of N2O. The preparation method comprises the following steps: dissolving biomass (agar) in water, adding a transition metal oxide soluble salt, heating and stirring for reaction, and after the reaction is finished, drying, grinding and calcining the obtained product to obtain a target product. The prepared catalyst takes a transition metal oxide as a catalytic main body, takes an improved sol-gel method as a preparation means, and assists the preparation of a high-activity transition metal oxide catalyst by adding low-price agar as a surface structure control agent of the catalyst, so that the performance of the catalyst for catalytically decomposing industrial waste gas N2O pollution is improved. According to the invention, chemical reaction between the agar and the transition metal oxide is utilized to achieve the purposes of increasing the specific surface area of the catalyst, destroying surface lattices and forming a large number of oxygen vacancies and lattice defects, so that the performance of the catalyst for catalytically decomposing N2O is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic decomposition of N2O, and specifically relates to a transition metal oxide catalyst with biomass as a surface structure controller and application thereof in low-temperature catalytic decomposition of N2O. Background Art

[0002] As a greenhouse gas, nitrous oxide (N2O) not only has a stronger global warming potential than CO2 and CH4, but also has a strong destructive power on stratospheric ozone. Nowadays, various anthropogenic activities such as nitric acid and adipic acid production, fossil fuel combustion, and automobile exhaust emissions have become the main sources of N2O emissions, and the total amount of emissions has been increasing year by year. Therefore, efficient catalytic decomposition of N2O under low temperature conditions to reduce the pollution caused to the environment is an urgent treatment method for mankind. Among the many methods for catalytic decomposition of N2O, direct catalytic decomposition has become an effective way to eliminate N2O due to its advantages such as simple equipment, low cost, and low energy consumption. So far, different types of catalysts, such as precious metal catalysts, transition metal oxide catalysts, and ion exchange zeolites, have been found to be used for the catalytic decomposition of N2O. Among them, transition metal oxide catalysts with transition metal oxides as active components are considered to be the most promising catalysts for direct catalytic decomposition of N2O due to their good redox properties, thermal stability, and cheap raw materials, and have great potential in the field of industrial decomposition of N2O.

[0003] In recent years, there have been quite a few reports on the topic of non-precious metal oxides. In particular, Co3O4 with a spinel structure exhibits excellent redox properties and oxygen vacancies. Due to its clear structure, convenient preparation, and affordable price, it is widely used in CO oxidation, CO2 hydrogenation, water oxidation, N2O decomposition and other fields. Due to its good redox properties and thermal stability, it is considered to be the most promising catalyst for direct catalytic decomposition of N2O.

[0004] Stelmachowski et al. (Catalysis Science & Technology, 2021, 11(11): 3737-3745) used different synthesis methods to prepare spinel Co3O4 with the same structure but different morphology. The resulting precursor was precipitated at 600°C and subsequently calcined to produce the material with the best catalytic activity, while the catalytic material produced by the hydrothermally prepared precursor under the same calcination procedure had the least ideal performance. The researchers found that the work function of the material is related to the changes in chemical properties caused by the morphology of the catalyst nanocrystals and the adsorption of gas-phase molecules. Catalysts with larger and stronger crystallinity have the lowest work function and the weakest ability to stabilize adsorbates, and therefore exhibit the highest catalytic activity.

[0005] Kang et al. (Catalysis Science & Technology, 2024) prepared a series of alkali / alkaline earth metal-doped Co3O4 spinel oxides for catalytic decomposition of N2O. The results show that the doping of alkali / alkaline earth metal ions causes lattice distortion of M-Co3O4, a decrease in grain size, an increase in specific surface area, and an increase in the number of active sites. Through a series of characterizations, it was found that the M-Co3O4 catalyst has a higher lattice oxygen mobility and is prone to forming more oxygen vacancies. These oxygen vacancies participate in the decomposition of N2O and synergistically promote the Co 2+ Reaction cycle at the active site.

[0006] Tursun et al. (Catalysis Communications, 2015, 65: 1-5) used a coprecipitation method to add large-radius metal Bi to Co3O4. The research and characterization found that the average grain size of Co3O4 was significantly reduced, and the specific surface area and active sites of the catalyst were significantly increased. x Co catalyst optimized Bi 0.02 On Co catalyst, at 400℃, 20000h -1 Under the GHSV condition of 1.3 GHSV, 2000 ppmv of N2O in Ar was completely decomposed. In addition, the catalyst showed strong resistance to CO2. At 400℃ and 10 vol.% CO2, the N2O conversion rate of the catalyst remained stable at more than 95%.

[0007] Nevertheless, in the field of direct catalytic decomposition of N2O catalysts, the traditional method of preparing Co3O4 catalysts has the disadvantages of low activity, complex process and high cost. In the above research background, the proposal and development of new catalyst preparation methods are particularly important. For transition metal oxides, surface defect sites play a vital role in the reaction as active sites for catalytic decomposition of N2O. How to increase the number of active sites of the catalyst and the performance of a single active site has become a breakthrough point for improving catalyst performance. Summary of the invention

[0008] In order to overcome the difficulty of cobalt-based oxide catalysts to have both high catalytic activity and strong resistance to NO x In order to solve the problem of the performance of impurity gases such as N2O, the present invention provides a transition metal oxide catalyst with biomass as a surface structure controller. The catalyst has a simple preparation process, good catalytic activity, good stability and can catalytically decompose N2O at low temperature.

[0009] In order to achieve this purpose, the technical solution provided by the present invention is as follows: a transition metal oxide catalyst with biomass as a surface structure controller, and the preparation method comprises the following steps: dissolving the biomass in water, adding a soluble salt of a transition metal oxide, heating and stirring the reaction, and after the reaction is completed, drying, grinding, and calcining the obtained product to obtain the target product.

[0010] Further, the biomass is agar (AG), the molecular formula of which is C 47 H 68 O 16 .

[0011] Furthermore, the soluble salt of the transition metal oxide is one or a combination of two or more of cobalt nitrate, cobalt acetate, cobalt oxalate, copper nitrate or nickel nitrate.

[0012] Furthermore, in molar ratio, biomass:transition metal oxide soluble salt=1:1-8.

[0013] Furthermore, the heating and stirring reaction is to stir the reaction at 50-90° C. for 1-3 hours.

[0014] Furthermore, the drying is performed at 80 to 140° C. for 6 to 18 hours.

[0015] Furthermore, the calcination is firstly calcined at 150-300°C for 0.5-1.5h, and then calcined at 350-450°C for 1-6h.

[0016] The invention provides an application of a transition metal oxide catalyst using biomass as a surface structure controller in low-temperature catalytic decomposition of N2O.

[0017] The beneficial effects of the present invention are:

[0018] 1. The present invention uses a biomass-assisted sol-gel method to prepare a transition metal oxide catalyst. The added biomass effectively reduces the crystal size of the catalyst, increases the specific surface area of ​​the catalyst, and increases the number of active sites accordingly, providing a large number of active sites for the catalytic decomposition of N2O. In addition, the addition of the catalyst surface structure controller AG also changes the surface properties of the catalyst, weakens the Co-O bond, and reduces the activation energy of the reaction.

[0019] 2. The transition metal oxide catalyst provided by the present invention has a transition metal oxide as an active component. The added biomass not only improves the activity of the Co3O4 catalyst in catalytically decomposing N2O, but also the prepared catalyst has good tolerance to impurity gases. Even in an atmosphere where 5vol% O2+100ppmv NO+2vol% H2O coexist, the catalyst provided by the present invention can achieve a conversion rate of nearly 51% for N2O (2000ppmv) in the reaction gas at 400°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The XRD analysis diagrams of the catalysts obtained in Examples 1-5 and Comparative Example 1 are shown.

[0021] Figure 2 The activity diagram of catalytic decomposition of N2O by the catalysts obtained in Examples 1-5 and Comparative Example 1 is shown.

[0022] Figure 3 This is an activity diagram of the catalyst obtained in Example 2 for catalytic decomposition of N2O at different temperatures in the presence of impurity gases (O2, H2O, NO).

[0023] Figure 4 This is a graph showing the stability of the catalyst obtained in Example 2 against impurity gases in the presence of impurity gases O2, NO, and H2O at 400°C.

[0024] Figure 5 The pore size distribution (A) and N2 physical adsorption-desorption isotherm (B) of the catalyst obtained in Example 2.

[0025] Figure 6 TEM images of the catalysts (A, C) obtained in Comparative Example 1 and the catalysts (B, D) obtained in Example 2. Specific implementation plan

[0026] In order to better understand the above-mentioned technical scheme, the technical scheme of the embodiments of the present application is described in detail below through the accompanying drawings and specific embodiments. It should be understood that the embodiments of the present application and the specific features in the embodiments are detailed descriptions of the technical scheme of the embodiments of the present application, rather than limitations on the technical scheme of the present application. In the absence of conflict, the embodiments of the present application and the technical features in the embodiments may be combined with each other.

[0027] According to a first aspect of an embodiment of the present invention, there is provided a transition metal oxide catalyst with biomass as a surface structure controller, and the preparation method comprises the following steps: dissolving the biomass in water, adding a soluble salt of a transition metal oxide, heating and stirring the reaction, and after the reaction is completed, drying, grinding, and calcining the obtained product to obtain a target product.

[0028] The present invention uses an improved sol-gel method as a preparation method, adds biomass as a surface structure controller of the catalyst, assists in the preparation of a high-activity transition metal oxide catalyst, effectively reduces the crystal size of the catalyst, increases the specific surface area of ​​the catalyst, and correspondingly increases the number of active sites, thereby providing a large number of active sites for the catalytic decomposition reaction of N2O.

[0029] In some feasible embodiments, further, the biomass is agar (AG), with a molecular formula of C 47 H 68 O 16 .

[0030] Agar (AG), obtained from marine algae, is one of the most important polysaccharides in biomacromolecules and has remarkable properties, such as high mechanical strength, biodegradability and biocompatibility. It is an extremely cheap and environmentally friendly biomass. In the present invention, the addition of agar can form a steric hindrance effect during the catalyst preparation process, and a certain number of defective active sites can be generated after being removed in the roasting stage. This agar-assisted catalyst synthesis method is not only simple in operation and low in cost, but the resulting catalyst also exhibits quite excellent catalytic activity. The present invention, through the addition of the catalyst surface structure controller AG, utilizes the chemical reaction between AG and the transition metal oxide, changes the surface properties of the catalyst, weakens the Co-O bond, and achieves the purpose of increasing the specific surface area of ​​the catalyst, destroying the surface lattice, and forming a large number of oxygen vacancies and lattice defects, thereby improving the performance of the catalyst in catalytic decomposition of N2O.

[0031] In some feasible embodiments, further, the transition metal oxide soluble salt is one or a combination of two or more of cobalt nitrate, cobalt acetate, cobalt oxalate, copper nitrate or nickel nitrate.

[0032] The invention adopts relatively cheap cobalt nitrate, cobalt acetate, cobalt oxalate, copper nitrate or nickel nitrate, thereby reducing the preparation cost of the catalyst as much as possible while ensuring the catalyst performance.

[0033] Too little or too much addition of biomass material agar will have an adverse effect on the performance of the prepared catalyst. In some feasible embodiments, further, the present invention preferably has a molar ratio of biomass: transition metal oxide soluble salt = 1:1-8, and the catalyst prepared at this molar ratio has good catalytic decomposition of N2O performance. Further, the present invention preferably has a molar ratio of biomass: transition metal oxide soluble salt = 1:3.6.

[0034] When the reaction temperature is lower than 50°C, agar is not easily dissolved; when the temperature is higher than 90°C, it is not conducive to the low-cost production of the subsequent catalyst. In some feasible embodiments, further, the present invention preferably heats and stirs the reaction conditions to stir the reaction at 50-90°C for 1-3 hours. Further, the present invention preferably heats and stirs the reaction conditions to stir the reaction at 90°C for 1 hour.

[0035] When the drying temperature is too high, the reactants are prone to react, and when the drying temperature is too low, the reactants are dried for a long time. In some feasible embodiments, further, the present invention preferably, the drying condition is to dry at 80 to 140 ° C for 6 to 18 hours. Drying under this condition, the resulting product can be completely dried within a given temperature and time range. Further, the present invention preferably, the drying condition is to dry at 120 ° C for 8 hours.

[0036] In order to ensure the microscopic morphology of the catalyst, in some feasible embodiments, further, the present invention preferably uses the calcination conditions of first calcining at 150-300°C for 0.5-1.5h, and then calcining at 350-450°C for 1-6h. Furthermore, the present invention preferably uses the calcination conditions of first calcining at 300°C for 1h, and then calcining at 450°C for 5h. Selecting 300°C as the calcination platform slows down the violent combustion process of the sample during calcination, which is conducive to maintaining the microscopic morphology of the catalyst.

[0037] A second aspect of the embodiments of the present invention provides the use of a transition metal oxide catalyst using biomass as a surface structure controller in the low-temperature catalytic decomposition of N2O.

[0038] The transition metal oxide catalyst with biomass as the surface structure controller provided by the present invention uses transition metal oxide as the catalytic main body and an improved sol-gel method as the preparation means. By adding low-cost agar (AG) as the surface structure controller of the catalyst, it assists in the preparation of a high-activity transition metal oxide catalyst. The prepared catalyst improves its performance in catalytic decomposition of N2O pollution in industrial waste gas. The prepared 1AG-Co3O4 catalyst has excellent low-temperature activity and good resistance to impurity gases. When 100ppmv NO, 5vol% O2 and 2vol% H2O are all introduced at 400°C, the N2O conversion rate can be stabilized at more than 51% for a long time (2000ppmv N2O / Ar, GHSV=20000h -1 ).

[0039] Example 1 Transition Metal Oxide Catalyst 0.5AG-Co3O4 (L(1))

[0040] The preparation method is as follows:

[0041] 0.5 g (0.0016 mol) of agar (AG) was added to a reaction vessel, and 50 mL of deionized water was added. The mixture was stirred and heated to 60°C. After the mixture was dissolved, 3.52 g (0.012 mol) of cobalt nitrate hexahydrate was added. The mixture was stirred and heated to 90°C. The mixture was stirred and reacted for 1 hour. After the reaction was completed, the mixture was placed in an oven with a fan, dried at 120°C for 8 hours, and then taken out. After grinding, the sample was heated to 300°C at a heating rate of 1°C / min, calcined at 300°C for 1 hour, and then heated to 450°C. The sample was calcined at 450°C for 5 hours to obtain a transition metal oxide catalyst with AG as a surface structure controller, named 0.5AG-Co3O4 and marked as L(1).

[0042] Example 2 Transition Metal Oxide Catalyst 1AG-Co3O4 (L(2))

[0043] The preparation method is the same as that of Example 1, except that 1 g (0.0033 mol) AG is used instead of 0.5 g AG in Example 1 to obtain a transition metal oxide catalyst with AG as a surface structure controller, named 1AG-Co3O4 and marked as L(2).

[0044] Example 3 Transition Metal Oxide Catalyst 1.5AG-Co3O4 (L(3))

[0045] The preparation method is the same as that of Example 1, except that 1.5 g (0.0049 mol) AG is used instead of 0.5 g AG in Example 1 to obtain a transition metal oxide catalyst with AG as a surface structure controller, named 1.5AG-Co3O4 and marked as L(3).

[0046] Example 4 Transition Metal Oxide Catalyst 2AG-Co3O4 (L(4))

[0047] The preparation method is the same as that of Example 1, except that 2 g (0.0065 mol) AG is used instead of 0.5 g AG in Example 1 to obtain a transition metal oxide catalyst with AG as a surface structure controller, named 2AG-Co3O4 and marked as L(4).

[0048] Example 5 Transition Metal Oxide Catalyst 3AG-Co3O4 (L(5))

[0049] The preparation method is the same as that of Example 1, except that 3 g (0.0098 mol) AG is used instead of 0.5 g AG in Example 1 to obtain a transition metal oxide catalyst with AG as a surface structure controller, named 3AG-Co3O4 and marked as L(5).

[0050] Comparative Example 1 Transition Metal Oxide Catalyst Co3O4(P) (B(1))

[0051] The preparation method is as follows:

[0052] First, take an appropriate amount of Co(NO3)2·6H2O and dissolve it in a certain amount of deionized water to prepare a 0.2M precursor solution for use. Subsequently, at 40°C, under continuous stirring, add 0.5M Na2CO3 precipitant dropwise to the above precursor solution to make the pH value of the solution reach 9.3. After aging for 2 hours, the resulting precipitate is filtered and washed with a large amount of deionized water to clean the residual sodium ions therein, and the pH value of the filtrate reaches neutral (pH=7) as the standard for cleaning the residual sodium ions. Finally, the resultant is placed in an oven at 110°C for drying, and after drying, it is calcined at 500°C in an air atmosphere for 3 hours to obtain a transition metal oxide catalyst, named Co3O4(P), and marked as B(1).

[0053] Example 6 Application of transition metal oxide catalysts in low temperature catalytic decomposition of N2O (I) XRD test of the transition metal oxide catalysts obtained in Examples 1-5 and Comparative Example 1

[0054] Catalysts L(1), L(2), L(3), L(4), L(5) and B(1) obtained in Examples 1-5 and Comparative Example 1 were characterized by XRD diffraction. Figure 1 .Depend on Figure 1 It can be seen that the XRD diffraction peaks of catalysts L(1), L(2), L(3), L(4), and L(5) show intact spinel structure Co3O4 crystal XRD diffraction peaks (JCPDS 43-1003) compared with B(1), which indicates that the catalyst prepared with biomass as the carrier only acts on the surface and does not destroy the bulk structure of Co3O4.

[0055] The grain size of Co3O4 in catalysts L(1), L(2), L(3), L(4), L(5) and B(1) was estimated according to the Scherrer formula, and the results are shown in Table 1. From the data in Table 1, it can be seen that for Co3O4, the average grain size is about 29nm. Compared with catalyst B(1), the average grain size of Co3O4 in catalysts L(1), L(2), L(3), L(4) and L(5) is reduced, such as the average grain size of catalyst L(2) is about 11nm. This shows that the grain size of Co3O4 in the catalysts prepared with biomass as the carrier is reduced.

[0056] Table 1

[0057]

[0058] (II) Effects of different transition metal oxide catalysts on low-temperature catalytic decomposition of N2O

[0059] The method is as follows: 0.2 g of the transition metal oxide catalyst (40-60 mesh) obtained in Examples 1-5 and Comparative Example 1 were weighed and placed in a quartz fixed bed reactor with an inner diameter of 4 mm, and pretreated at 450°C for 30 min under Ar atmosphere. The bed temperature was lowered to the desired reaction temperature (450°C, 400°C, 350°C or 300°C), 2000 ppmv of N2O / Ar was introduced into the reaction tube, and the total gas flow rate was 50 mL·min -1 After 20 minutes of reaction, the mixed gas obtained after the reaction was sampled through a six-way valve, and the concentration of residual N2O in the mixed gas was analyzed by gas chromatograph (stationary phase Porapak Q, thermal conductivity cell detector), and the conversion rate of N2O catalytic decomposition by catalysts L(1)-L(5) and B(1) at each reaction temperature was calculated. The results are as follows: Figure 2 shown.

[0060] Depend on Figure 2 It can be seen that the xAG-Co3O4 catalyst prepared with AG as the carrier has better activity in catalytic decomposition of N2O than pure Co3O4. With the increase of the mass of AG used, the catalytic activity shows a "volcano-type" trend, and the catalytic activity is optimal at 1AG-Co3O4. That is, the transition metal oxide catalyst L(2) has the best catalytic activity.

[0061] (III) Testing the Impurity Gas Tolerance of the Most Active Catalyst (L(2))

[0062] Whether the catalyst has good resistance to impurity gases plays a decisive role in whether it can be used in actual industrial production. Therefore, the resistance of catalyst 1AG-Co3O4 to impurity gases (NO, O2 and H2O) discharged from nitric acid plants was evaluated. The results are as follows: Figure 3 When no impurity gas is introduced into the system, the T 90 (Temperature when N2O conversion reaches 90%) is about 387°C; when 100ppmv NO, 5vol.% O2 and 2vol.% H2O enter the reaction system, the corresponding T 90 380℃, 402℃, 396℃, respectively, all increased to varying degrees, which means that NO, O2 and H2O all inhibited the activity of the catalyst, but the inhibitory effect was relatively limited. In addition, when all impurity gases (100ppmv NO, 5vol.% O2 and 2vol.% H2O) were introduced into the reaction system, the N2O conversion rate of catalyst L(2) could reach more than 50% at 400℃.

[0063] (IV) Stability test of the most active catalyst (L(2))

[0064] Under the specified reaction conditions, the N2O conversion rate on the catalyst 1AG-Co3O4 changes with time to determine the stability of the catalyst. The results are as follows Figure 4 First, without any impurity gas introduced, the conversion rate of the catalyst at 400°C was always maintained at 100%; then 5 vol.% O2, 100 ppmv NO and 2 vol.% H2O were introduced in sequence, and the conversion rate of the catalyst dropped to 59% after 4 hours, and finally maintained at around 51% after 16 hours of continuous introduction; then all impurity gases were cut off one by one, and it was found that the catalyst conversion rate finally recovered to 100% and remained stable.

[0065] (V) The N2 physical adsorption-desorption isotherms and pore size distribution of the catalyst with the best activity (L(2)) and the catalyst B(1) obtained in comparative example 1 were analyzed.

[0066] The catalysts L (2) and B (1) obtained in Example 2 and Comparative Example 1 were characterized by N2- physical adsorption and desorption. The corresponding results are listed in Tables 1 and Figure 5 .

[0067] The data in Table 1 show that the specific surface area of ​​catalyst L (2) is 43 m 2 / g, which is about 3 times that of catalyst B (1).

[0068] from Figure 5 As can be seen in Figure 2, the N2 adsorption-desorption isotherm (B) of catalyst L(2) shows a typical type IV isotherm unique to mesoporous materials. Its pore size distribution diagram (A) also shows that there is a certain mesoporous structure around 17.32nm, and the pore volume is about 0.232cm 3 / g. This means that when using biomass as a carrier to prepare Co3O4 catalyst, it tends to corrode larger grains. In the erosion process, it does not erode layer by layer, but rather performs drilling corrosion at a certain weak site, thereby greatly increasing the specific surface area of ​​the catalyst and the number of reactive active sites.

[0069] (VI) Transmission electron microscopy analysis of the most active catalyst (L(2)) and the catalyst obtained in comparative example 1 (B(1))

[0070] Figure 6 TEM photos of catalyst L (2) and catalyst B (1) obtained in Example 2 and Comparative Example 1. Figure 6 It can be seen from Figures A and C that the grain size of catalyst B (1) (pure Co3O4) varies greatly, ranging from 22nm to 50nm, with an average grain size of 29nm, which is consistent with the results of XRD characterization. Compared with catalyst B (1), the grain size distribution of Co3O4 in catalyst L (2) is more concentrated, basically maintained at around 12nm, such as Figure 6 As shown in B. That is to say, the catalyst prepared with biomass as the carrier disintegrates the larger particles in the pure Co3O4 catalyst, so that they are all maintained at about 12nm. Figure 6 Figure D shows a higher magnification TEM image of the 1AG-Co3O4 catalyst. Figure 6 Compared with C in the middle, it can be clearly found that there are obvious defects on the surface of the catalyst grains. This means that the catalyst made with biomass as the carrier does increase the defect sites on the catalyst surface in the microstructure, providing abundant active sites for improving the catalyst reaction.

[0071] The 1AG-Co3O4 catalyst prepared by the present invention has excellent low temperature activity and good resistance to impurity gases. When 100ppmv NO, 5vol% O2 and 2vol% H2O are all introduced at 400°C, the N2O conversion rate can be kept stable at more than 51% for a long time (2000ppmv N2O / Ar, GHSV=20000h -1 ). In the present invention, the chemical reaction between AG and transition metal oxide is used to increase the specific surface area of ​​the catalyst, destroy the surface lattice, and form a large number of oxygen vacancies and lattice defects, thereby improving the performance of the catalyst in catalytic decomposition of N2O.

[0072] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A transition metal oxide catalyst with biomass as a surface structure control agent, characterized in that: The preparation method comprises the following steps: dissolving biomass in water, adding transition metal oxide soluble salt, heating and stirring for reaction, and after the reaction is completed, drying, grinding and calcining the obtained product to obtain the target product.

2. A transition metal oxide catalyst with biomass as a surface structure control agent according to claim 1, characterized in that: The biomass is agar, and the molecular formula is C 47 H 68 O 16 .

3. A transition metal oxide catalyst with biomass as a surface structure control agent according to claim 1 or 2, characterized in that: The soluble salt of transition metal oxide is one or a combination of two or more of cobalt nitrate, cobalt acetate, cobalt oxalate, copper nitrate or nickel nitrate.

4. A transition metal oxide catalyst with biomass as a surface structure control agent according to claim 3, characterized in that: In terms of molar ratio, biomass: soluble salt of transition metal oxide = 1:1-8.

5. A transition metal oxide catalyst with biomass as a surface structure control agent according to claim 1 or 2, characterized in that: The heating and stirring reaction is to stir the reaction at 50-90° C. for 1-3 hours.

6. A transition metal oxide catalyst with biomass as a surface structure control agent according to claim 1 or 2, characterized in that: The drying is performed at 80 to 140° C. for 6 to 18 hours.

7. A transition metal oxide catalyst with biomass as a surface structure control agent according to claim 1 or 2, characterized in that: The calcination is firstly calcined at 150-300°C for 0.5-1.5h, and then calcined at 350-450°C for 1-6h.

8. Use of the transition metal oxide catalyst with biomass as surface structure controller as claimed in claim 1 or 2 in low temperature catalytic decomposition of N2O.

Citation Information

Cited By

  • Preparation method of pectin-assisted high-activity transition metal oxide catalyst and application of pectin-assisted high-activity transition metal oxide catalyst in catalytic decomposition of N2O

    CN120939943A